Allogeneic immunotherapy for relapsed multiple myeloma: role of matched unrelated donors - Görner, Martin; Höpfner, Sabine; Goldschmidt, Hartmut; Ho, Anthony Dick (The Chinese-german journal of clinical oncology, 2002)
Existence of a graft-versus-myeloma effect has been well documented by responses to donor lymphocyte infusions and longterm survival after allogeneic bone marrow transplantation. The development of non-myeloablative conditioning regimens allows utilization of allogeneic effects in patients usually not suitable for myeloablative allogeneic transplantation, such as older and heavily pretreated patients. In a small series of 11 patients with multiple myeloma relapsing after autologous transplantation, we show that conditioning with low-dose total body irradiation in combination with fludarabine allows stable engraftment after matched unrelated donor transplantation and is tolerated with acceptable transplant-related morbidity and mortality. With a short median follow-up of 225 days, disease control was achieved only for patients responding to conventional treatment prior to allografting. Future studies with longer follow-up have to define the role of non-myeloablative allogeneic transplantation from unrelated donors as consolidation for patients responding to salvage therapy.